Loss of the modifiers of variegation Su(var)3-7 or HP1 impacts male X polytene chromosome morphology and dosage compensation. - Spierer, A.; Seum, C.; Delattre, M.; Spierer, P. (Journal of Cell Science, 2005)
Loss of Su(var)3-7 or HP1 suppresses the genomic silencing of position-effect variegation, whereas over-expression enhances it. In addition, loss of Su(var)3-7 results in preferential male lethality. In polytene chromosomes deprived of Su(var)3-7, we observe a specific bloating of the male X chromosome, leading to shortening of the chromosome and to blurring of its banding pattern. In addition, the chromocenter, where heterochromatin from all polytene chromosomes fuses, appears decondensed. The same chromosomal phenotypes are observed as a result of loss of HP1. Mutations of Su(var)3-7 or of Su(var)2-5, the gene encoding HP1, also cause developmental defects, including a spectacular increase in size of the prothoracic gland and its polytene chromosomes. Thus, although structurally very different, the two proteins cooperate closely in chromosome organization and development. Finally, bloating of the male X chromosome in the Su(var)3-7 mutant depends on the presence of a functional dosage compensation complex on this chromosome. This observation reveals a new and intriguing genetic interaction between epigenetic silencing and compensation of dose.